The relationship between heparanase levels, thrombus burden and thromboembolism in patients receiving unfractionated heparin treatment for prosthetic valve thrombosis - (:unkn) unknown (PERGAMON-ELSEVIER SCIENCE LTD, 2018)
Introduction: Procoagulant activity of heparanase has been recently described in several arterial and venous thrombotic disorders. In this study, we aimed to investigate the role of heparanase with regard to thrombus burden, thromboembolism, and treatment success with unfractionated heparin (UFH) in patients with prosthetic valve thrombosis (PVT). Methods: This study enrolled 79 PVT patients who received UFH for PVT and 82 controls. Plasma samples which were collected from patients both at baseline and after the UFH treatment and from controls at baseline only, were tested for heparanase levels by heparanase enzyme-linked immunosorbent assay. Results: The PVT group included 18 obstructive and 61 non-obstructive PVT patients who received UFH infusions for a median duration of 15 (7-20) days. The UFH treatment was successful in 37 (46.8%) patients. Baseline heparanase levels were significantly higher in the patient group than in the controls [0.29 (0.21-0.71) vs. 0.25 (0.17-0.33) ng/mL; p = 0.002]. Baseline heparanase levels were significantly higher in obstructive PVT patients. There was a significant increase in heparanase levels after UFH treatment. Post-UFH heparanase levels were higher in patients who experienced treatment failure compared to successfully treated group. Baseline and post-UFH heparanase levels were significantly higher in patients with a thrombus area >= 1 cm(2) and with a recent history of thromboembolism. Conclusions: Increased heparanase levels may be one of the esoteric causes for PVT. UFH treatment may trigger an increase in heparanase levels which may affect the treatment success. Increased heparanase levels may be associated with high risk of thromboembolism and increased thrombus burden in PVT patients.
Keywords: Echocardiography; Heparanase; Prosthetic valve thrombosis; Thromboembolism; Unfractionated heparin; PROCOAGULANT ACTIVITY; THROMBOLYTIC THERAPY; ECHOCARDIOGRAPHY; RECOMMENDATIONS; MANAGEMENT; SURGERY; TEE